KEBOCORAN TEPI RESTORASI RESIN KOMPOSIT NANOHYBRID SETELAH PERENDAMAN DALAM AIR SUNGAI DESA ANJIR PASAR - Kurniawan, Panji; Erlita, Isyana; Ichrom Nahzi, Muhammad Yanuar (Dentino, 2017)
ABSTRACTBackground: Composite resin is broadly used by dental practitioners as restoration material to treat caries. Nanohybrid composite resin is a type of composite resin composed of nano-size filler combined with larger filler. Composite resin has water absorption characteristic which tends to solute when it reacts with acid (low pH). Result from both of those characteristics is formation of a gap between restoration and cavity edge, which eventually leads to micro-leakage. Purpose: The aim of this study was to assess and measure the rate of nanohybrid composite resin micro-leakage as a result of submersion in water with acid characteristic (low pH). Methode: This study was a true experimental using posttest-only with control group design. Samples used were 20 maxillary premolars, divided into 2 groups: river water immersion which has acid characteristic (low pH) as treatment group, and sterile aquades immersion which has neutral characteristic (pH 7) as control group. Result: The result of Mann-Whitney showed a significant difference between the treatment group with the mean score of 4,00 and control group with the mean score of 3,00. Conclusion: Based on the study it can be concluded that there was a significant difference in micro-leakage effect of river water immersion and sterile aquades immersion on nanohybrid resin composite restorasion.Keywords: nanohybrid composite resin, acid pH, micro-leakage.